Pendampingan Penyusunan Strategi Digital Marketing Untuk Meningkatkan Daya Saing Umkm Kuliner Di Kabupaten Tasikmalaya - Ricky Hermayanto; Lati Sari Dewi; Siti Amirah Makarim (CV. SINAR HOWUHOWU, 2026)
The development of digital technology has transformed the marketing practices of micro, small, and medium enterprises (MSMEs). However, many MSMEs still lack the ability to optimally utilize digital media to increase sales. This community service activity aims to improve the knowledge and skills of culinary MSMEs in implementing digital marketing strategies. The methods used included observation, training, mentoring, and evaluation. Twenty-five culinary MSMEs in Tasikmalaya Regency participated in the activity. The materials provided included an introduction to digital marketing, the use of social media, promotional content creation, copywriting, and the use of WhatsApp Business. The results of the activity showed an increase in participants' understanding of digital marketing, their ability to create more engaging promotional content, and their increased use of social media as a marketing tool. This mentoring program had a positive impact on increasing the marketing capacity of MSMEs, enabling them to expand their market reach and enhance their competitiveness. This finding aligns with various community service programs that demonstrate that digital marketing training and mentoring can improve MSMEs' digital literacy and marketing capabilities.